PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS BRAIN BASED LEARNING PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL UNTUK KELAS VIII SMP - Marda, Muthia Marda (Jurnal Edukasi dan Penelitian Matematika, 2023)
Teaching materials are very important supporting media in learning, one of whichis Student Worksheets. In addition to the teaching materials, the model used must also be in accordance with the chacracteristics of students. The purpose of this study is to develop student worksheets based on Brain Based Learning (BBL) on one of the mathematics materials, the system of two-variable linear Equations for class VIII of the Junior High School. The model used in this study is the plomp development model. Based on the validity analysis results, the validity percentage is 88,75% with a very valid category. Whereas, pracricality test results obtained 88,54% in the very  practical category. Based on the results obtained, it can be concluded that the student worksheets based on brain based learning on the system of linear equations in two variables material for class VIII of junior high school are valid and practical. Keywords– Brain Based Learning, Student worksheets, Junior High School, The System of Linear Equations in Two Variables